Escape from Sobibor. - Rashke, Richard (Delphinium Books, 2015)
Revised and Updated "Brilliantly reconstructs the degradation and drama of Sobibor. . . . A memorable and moving saga, full of anger and anguish, a reminder never to forget." -San Francisco Chronicle On October 14, 1943, six hundred Jews imprisoned in Sobibor, a secret Nazi death camp in eastern Poland, revolted. They killed a dozen SS officers and guards, trampled the barbed wire fences, and raced across an open field filled with anti-tank mines. Against all odds, more than three hundred made it safely into the woods. Fifty of those men and women managed to survive the rest of the war. In thi.